2015
DOI: 10.1080/10916466.2015.1060500
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Surface Activity of Some Schiff Base Cationic Surfactant Complexes Against Different Microorganisms

Abstract: In this study, different metallocationic surfactants were prepared by reaction of N,N dimethyl ethylene diamine with benzaldehyde (Schiff base reaction) then quaternized the resulted tertiary amines with different alkyl halides such as dodecyl bromide and hexadecyl bromide to produce a series of quaternary ammonium salts. Finally, complexing the cationic surfactants with stannous chloride and cobalt chloride to give the corresponding metallocationic surfactants. Surface tension of these surfactants at four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The n value is around 0.86 when DHSiMF and DHSiB are absent. The formation of impurities, roughness, crystalline network flaws, active site size and irregular distribution, and other surface defects have all been connected to surface heterogeneity, which has been shown to be clearly visible at n values smaller than one 44 . The n values show that the presence of these chemicals impaired surface homogeneity because they were present in higher concentrations than those in the corrosive media without inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The n value is around 0.86 when DHSiMF and DHSiB are absent. The formation of impurities, roughness, crystalline network flaws, active site size and irregular distribution, and other surface defects have all been connected to surface heterogeneity, which has been shown to be clearly visible at n values smaller than one 44 . The n values show that the presence of these chemicals impaired surface homogeneity because they were present in higher concentrations than those in the corrosive media without inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The standard adsorption free energy (Δ G ads o ) can be calculated using the mathematical eq . where R is the universal gas constant, and the value 55.5 represents the theoretical molar concentration of water. The calculated negative Δ G ads values listed in Table showed that the Pz1 and Pz2 adsorptions would be of a spontaneous nature.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the fact that this is the method of the biocidal potent as a surfactant, the linked zone of the germicidal agent is obscure [45]. Growing the concentration of the biocide leading to more aggregate at varied substrates (aqueous or films of microorganism) [46]. Thus, the more collection of the nonionic surfactants at the film of the cells leading to excess of vigorous act of the molecules toward microorganisms.…”
Section: Maximum Surface Excess (Max)mentioning
confidence: 99%